Encephalitis-Associated Hospitalizations among American Indians and Alaska Natives - Mehal, Jason M. (The American Society of Tropical Medicine and Hygiene, 2014)
Encephalitis produces considerable morbidity in the United States, but morbidity rates among American Indian/Alaska Native (AI/AN) people have not been described. Hospitalization records listing an encephalitis diagnosis were analyzed by using Indian Health Service direct/contract inpatient data. For 1998–2010, there were 436 encephalitis-associated hospitalizations among AI/AN people, an average annual age-adjusted hospitalization rate of 3.1/100,000 population. The rate for infants (11.9) was more than double that for any other age group. Death occurred for 4.1% of hospitalizations. Consistent with reports for the general U.S. population, the rate was high among infants and most (53.9%) hospitalizations were of unexplained etiology. The average annual rate during the study period appeared lower than for the general U.S. population, due particularly to lower rates in the elderly. Future community-based surveillance and mortality studies are needed to confirm these findings and examine reasons underlying the low rates of encephalitis in AI/AN people.